2006
DOI: 10.1073/pnas.0608896103
|View full text |Cite
|
Sign up to set email alerts
|

A 50-kDa ERK-like protein is up-regulated by a dual altered peptide ligand that suppresses myasthenia gravis-associated responses

Abstract: Myasthenia gravis (MG) and its animal model, experimental autoimmune MG (EAMG), are T cell-dependent antibody-mediated autoimmune diseases. A dual altered peptide ligand (APL) that is composed of the tandemly arranged two single amino acid analogues of two myasthenogenic peptides, p195-212 and p259 -271, down-regulated in vitro and in vivo MG-associated autoreactive responses. The dual APL was shown to exert its beneficial effects by up-regulating ERK1,2 in CD4 ؉ CD25 ؉ regulatory cells. In this study, we inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…Blocking of PDGFRα+β leads to changes in ERK and, further downstream, the increase of hexokinase-2 expression resulting in higher metabolic glucose demand as measured with [ 18 F]FDG. Changes in pERK levels and altered ERK isofroms have been documented previously with our work on changes in PDGFRA signalling and blockade (Ekpe et al 2016), as well as by Ben-David et al (2006) and Sabbatino et al (2014). The relationship between ERK signalling and [18F]FDG uptake has also been well documented in clinical analysis of MEK inhibitors in different metastatic solid tumours, whereby decreased ERK activity follows a reduction in [ 18 F]FDG uptake (Kraeber-Bodéré et al 2012).…”
Section: Discussionsupporting
confidence: 75%
“…Blocking of PDGFRα+β leads to changes in ERK and, further downstream, the increase of hexokinase-2 expression resulting in higher metabolic glucose demand as measured with [ 18 F]FDG. Changes in pERK levels and altered ERK isofroms have been documented previously with our work on changes in PDGFRA signalling and blockade (Ekpe et al 2016), as well as by Ben-David et al (2006) and Sabbatino et al (2014). The relationship between ERK signalling and [18F]FDG uptake has also been well documented in clinical analysis of MEK inhibitors in different metastatic solid tumours, whereby decreased ERK activity follows a reduction in [ 18 F]FDG uptake (Kraeber-Bodéré et al 2012).…”
Section: Discussionsupporting
confidence: 75%
“…A functional impairment of thymic Treg cells was found in the thymus of MG patients and may thus be involved in the onset of the autoimmune process (14). CD4 ϩ CD25 ϩ cells were found to be functionally involved in the suppressive action of various effective therapies demonstrated by us and by others in the mouse and rat experimental models for MG (15)(16)(17)(18)(19)(20), suggesting that modulation of the CD4 ϩ CD25 ϩ cell compartment could play a key role in the treatment of myasthenia. The knowledge on Treg cell induction and activation opens the possibility of an attractive approach for immunotherapy of autoimmune diseases.…”
Section: Most Endogenous Cd4mentioning
confidence: 99%
“…Different alternatively spliced forms were also reported for ERK5 (Yan et al 2001), MEK5 (English et al 1995), JNK (Gupta et al 1996), MKK7 (Tournier et al 1999), and others. In addition, besides ERK1c, two alternatively spliced forms-ERK1b (Yung et al 2000) and ERK2b (Gonzalez et al 1992)-have been reported for ERKs, and other forms may exist as well (Ben-David et al 2006). Thus, alternatively spliced isoforms of components of MAPK cascades add to the complexity of the signaling network, which allows the regulation of the wide range of processes governed by these cascades.…”
Section: Mek1b-erk1c Is An Erk Cascade Subroutementioning
confidence: 99%